Visualizing dynamic (after)taste effects by means of time‐discrete TCATA data analysis. Issue 3 (15th February 2022) - Derks, Eduard; Ramnarain, Shalla; Zhang, Tristan; van Doorn, Rudi; Nijmeijer, Marieke; van den Berg, Marco
Abstract: A time‐discrete temporal check‐all‐that‐apply (TCATA) data analysis method was implemented and applied to two different commercial use cases: (I) exploration of the dynamic sensory effects evoked by sweetened yogurt, and (II) a dynamic flavor profile comparison of nutritionally fortified gummy bears. The purpose of the first study was to explore opportunities for calorie reduction while maintaining the original dynamic sensory profile. The purpose of the second study was to benchmark commercially available fortified candy for (after)taste. The resulting time‐discrete data were fitted with Poisson regression allowing means for computing confidence intervals for each discrete time bucket. A roughness penalty was added to impose smoothness to the fitted TCATA profiles. Both studies demonstrated improved visualization and revealed underlying dynamic sensory insights which were hidden in conventional TCATA profiles based on the primary data. Practical Applications: Temporal sensory effects—determining onset, intensity, and duration (aka lingering) of various attributes—are key for consumer acceptance of new food products. However, cross‐modal interactions and the complexity of sensory attributes can limit the discrimination between different products. This study established a generic toolbox to process raw temporal (i.e., TCATA) data and improve visualization and discrimination. These results help to quantify and identify possible methodologies to improve ingredient applications for healthy foods (e.g., sugar reduction, nutrient fortification). The tool is available for analyzing TCATA data acquired with commercially available sensory data acquisition software products like EyeQuestion, FIZZ, and Compusense.